Analysis of the Correlation Between Waiting Time for Prescription Services and Patient Satisfaction in Puskesmas - Yuswantina, Richa; Dyahariesti, Niken; Falkhatiana, Wilda; Syari, Nyayu Ayunda (Universitas Islam Lamongan, 2022)
Efforts to improve and control the quality of pharmaceutical services to ensure patient satisfaction are carried out by evaluating the waiting time for prescription services in preparing pharmaceutical preparations and the level of patient satisfaction in pharmaceutical services [1]. Puskesmas is the first level health facility that participates in efforts to achieve the target of Minimum Service Standards [2]. The purpose of this study was to analyze the relationship between waiting time for prescription services and the level of patient satisfaction at the Puskesmas. This study used an observational research design with a design approach cross sectional. Determination of the research sample using a purposive sampling method. Analysis of the data used for this research is univariate analysis and bivariate analysis, as well as statistical chi-square test.Results: This study used an observational research design with a cross sectional design approach. Analysis of the data used for this study using the SPSS program, as well as the chi-square statistical test. According to standard waiting time for prescription service, 155 recipes (92.90%) were categorized according to standard and 11 prescriptions (7.10%) were not according to standard. The level of satisfaction of respondents was categorized as satisfied as many as 132 respondents (85.16%) while those who felt dissatisfied were 23 respondents (14.84%). From the results of the analysis of the chi-square test waiting time and the level of patient satisfaction obtained P Value <0.05.There is a relationship between waiting time for prescription services and the level of patient satisfaction at the Puskesmas.